2012
DOI: 10.1212/wnl.0b013e318249f71f
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous c.14576G>A variant of RNF213 predicts early-onset and severe form of moyamoya disease

Abstract: The homozygous c.14576G>A variant in RNF213 could be a good DNA biomarker for predicting the severe type of MMD, for which early medical/surgical intervention is recommended, and may provide a better monitoring and prevention strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
229
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(267 citation statements)
references
References 26 publications
18
229
8
Order By: Relevance
“…There is little knowledge of how genes contribute to moyamoya syndrome, probably because of its multifactorial nature and also because of the heterogeneity of the associated genetic disorders. Mutations in the RNF213 gene, which are now recognized as a risk factor and that are associated with aggressive moyamoya, were not found [13,14]. This is in agreement with the relatively late and benign disease shown here.…”
Section: Discussionsupporting
confidence: 91%
“…There is little knowledge of how genes contribute to moyamoya syndrome, probably because of its multifactorial nature and also because of the heterogeneity of the associated genetic disorders. Mutations in the RNF213 gene, which are now recognized as a risk factor and that are associated with aggressive moyamoya, were not found [13,14]. This is in agreement with the relatively late and benign disease shown here.…”
Section: Discussionsupporting
confidence: 91%
“…It is suggested that the incidence rate of MMD is relatively low if one had the heterozygous variant, whereas incidence rate for homozygotes are extremely high (478%). 6 This also reflects the effect of this variant with the dose effect.…”
mentioning
confidence: 91%
“…4 In addition, c.14576G4A homozygotes exhibit more severe and wider vasculopathy than heterozygotes. 6 Here, we present sibling cases of MMD having homozygous and heterozygous c.14576G4A variant in RNF213, as well as different clinical course and disease severity.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…7 Evidence suggests that RNF213 gene on chromosome 17q25.3 is an important predisposing factor for MMD in East Asian populations. [8][9][10][11][12][13] The disease is most common in children and young adolescents, with two peaks of incidence: the first decade of life and the third decade of life.…”
Section: Discussionmentioning
confidence: 99%